Influence Factors of Capital and Entrepreneurial Succes in Small Industries - Maya Salindeho (Journal of International Conference Proceedings (JICP), 2018)
This study aims to get an overview of the influence of capital and entrepreneurship factors in improving the success of small industries, with the research design used in this study is survey research and causality studies because it has the aim to analyze whether there is a reciprocal influence between capital and entrepreneurship variables on the success of development small industry. The population in this study were small industrial entrepreneurs in Bitung. totaling 344 small industries and a sample of 185 small industries were taken (DISPERINDAKOP BITUNG). To analyze research data, use descriptive and inferential statistical techniques. Descriptive statistics are intended to provide a description of the research variables, namely average and standard deviation, media, and frequency tables and percentage analysis. Inferential statistics are intended for model validation analysis used to test hypotheses. To test the hypothesis presented in this study used Structural Equation Modeling (SEM) approach. (Solimun, 2002). The results show that: First, the effect of the coefficient of capital variable (X1) on the success of small industry (Y) is 0.308 with the value of t is 5.033 from the significance level of 0.000. The coefficient shows that the variable capital (X1) has a positive influence on the success of small industries (Y). This means that an increase in capital (X 1), will be followed by an increase in the success of small industries (Y) assuming other factors that affect the success of small industries (Y) are considered constant. The statistic value t_count shows the effect of capital (X1) for the success of small industry (Y) is 5.033 with a significance level of 0000 or below 0.05. This means that capital (X1) has a significant influence on the success of small industries (Y). Second, the influence of entrepreneurship variable coefficient (X 2) on the success of small industry (Y) of 0.232 with a t-count of 4.2333 from the significance level of 0.000. The coefficient shows that the entrepreneurshipl variable (X2) has a positive effect on the success of small industries (Y). This means that increasing entrepreneurship (X 2), will be followed by an increase in the success of small industries (Y) by assuming that other factors that affect the success of the small industry (Y) are considered constant. Statistical value t arithmetic shows the influence of entrepreneurship (X 2) on the success of small industry (Y) of 4.233 with a significance of 0000 or below 0.05. This means that entrepreneurship (X2) has a significant effect on the success of small industries (Y). Thus it can be concluded that capital and entrepreneurship have a positive and significant effect on the success of small industry development. This shows that small business development, capital and entrepreneurship are factors that are very influential in the successful development of small industries. Keywords: Capital, Entrepreneurship, Small Industries